Faktor-faktor yang Mempengaruhi Kinerja Kualitas, Kinerja Keuangan dan Kepuasan Pelanggan - Murwaningsari, Etty; Basaria, Maya Grace; Rachmawati, Sistya (Jurnal Aplikasi Manajemen, 2009)
The objective of this research is to investigate factors affecting quality performance, financial performance, and customer satisfaction. Those factors consist of quality goal, quality feedback, and quality incentive. The research examined 20 manufacturing companies listed in Indonesia stock exchange in 2007. The primary data were collected by questionnaire, and the number of respondent are 69 manager. The statistical method used to test the hypothesis is path analysis model. The empirical result of this research shows that: fist, quality goal and incentive based in quality have positive relationship with quality performance. Second, quality performance has positive relationship with customer satisfaction and financial performance. Third, customer satisfaction variable has positive relationship with financial performance. Meanwhile, quality goal is affecting quality performance variable and then quality performance is affecting customer satisfaction. The other variables have no significant relationship.